THE IMPERATIVE OF STATE FINANCIAL RESTITUTION IN ANTI-CORRUPTION ERADICATION MEASURES - Putra, Muhamad Gempa Awaljon; Usman, Dr. Usman; Satoto, Prof. Dr. Sukamto (jfpublisher, 2024)
Corruption is defined as a white-collar crime that mostly affects public authorities. In addition, corruption is categorized as an outstanding crime because it obstructs the people’s economy and national development. Uncontrollable corrupt practices will have a comprehensive impact on a country’s government system and can serve to further disrupt future governance. Therefore, the restoration and return of state financial losses from corruption is a high priority in upholding legislation and penal law in Indonesia. The objective of this research is examine several corruption crimes in Indonesia, their eradication efforts, and state governments’ attempts in restitution of state financial losses caused by corruption offenses. A normative juridical research method was used in this research, combined with legislative approach, case approach, comparison approach, and theoretical approach. The research concluded that corruption offenses are divided into seven categories of offenses that can lead to losses of state finances. The eradication of on Indonesia's corruption has been realized since the New Order until now.